Comparison of insertion and functional gain in hearing aid users - C, Niladri Shankar Roy (Journal of All India Institute of Speech and Hearing)
The study was undertaken to investigate whether functional gain and insertion gain measures were comparable in body level hearing aid users. The data was collected from fifteen subjects (twenty five ears) having moderateto- severe degree of sensori-neural hearing loss. The data was collected in a clinical setting. Separate sound treated rooms were used to measure the functional gain and the insertion gain. Both the measurements were done at 0° azimuth with the speaker distance and height kept constant from the subjects.